Quantitative characterization of topographic defects of semiconductor silicon wafers - S. F. Sianko; A. S. Sianko; V. A. Zelenin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The calculation of shadow images of the surfaces of semiconductor silicon wafers obtained by Makyoh topography is carried out. A quantitative relationship between the intensity of the shadow spots on the topogram and the micro geometric parameters of the silicon wafers has been established. The software for quantitative 3D-control and control criteria of the silicon wafer surfaces is proposed.